Experimental and Theoretical Study on Crown Ether-Appended-Fe(III) Porphyrin Complexes and Catalytic Oxidation Cyclohexene with O2 - Xiaodong Li; Ailing Feng; Yanqing Zu; Peitao Liu; Fengbo Han (Molecules, 2023)
Modifying non-precious metal porphyrins at the meso-position is sufficient to further improve the ability to activate O2 and the selectivity of the corresponding redox products. In this study, a crown ether-appended Fe(III) porphyrin complex (FeTC4PCl) was formed by replacing Fe(III) porphyrin (FeTPPCl) at the meso-position. The reactions of FeTPPCl and FeTC4PCl catalysed by O2 oxidation of cyclohexene under different conditions were studied, and three main products, 2-cyclohexen-1-ol (1), 2-cyclohexen-1-one (2), and 7-oxabicyclo[4.1.0]heptane (3), were obtained. The effects of reaction temperature, reaction time, and the addition of axial coordination compounds on the reactions were investigated. The conversion of cyclohexene reached 94% at 70 °C after 12 h, and the selectivity toward product 1 was 73%. The geometrical structure optimization, molecular orbital energy level analysis, atomic charge, spin density, and density of orbital states analysis of FeTPPCl, FeTC4PCl, as well as the oxygenated complexes (Fe-O2)TCPPCl and (Fe-O2)TC4PCl formed after adsorption of O2, were carried out using the DFT method. The results of thermodynamic quantity variation with reaction temperature and Gibbs free energy variation were also analysed. Finally, based on experimental and theoretical analysis, the mechanism of the cyclohexene oxidation reaction with FeTC4PCl as a catalyst and O2 as an oxidant was deduced, and the reaction mechanism was obtained as a free radical chain reaction process.